Factors of Diabetic Retinopathy among Type 2 Diabetes Mellitus Patients in Central Java Province, Indonesia - Casmuti, Casmuti; Zainafree, Intan; Cahyati, Widya Hary; Ningrum, Dina Nur Anggraini; Saefurrohim, Muhamad Zakki; Hakam, Abdul; Zaimatuddunia, Irma; Prasetya, Henky Yoga; Jusran, Alek; Irsam, Muhamad (Unnes Journal of Public Health, 2025)
One of the microvascular complications of type 2 diabetes mellitus is diabetic retinopathy. The prevalence of diabetes mellitus in Central Java Province in 2022 by 10% increased to 12.52% in the third quarter of 2023. This prevalence rate has not reached the SDG's target, namely there is no increase in diabetes prevalence by 0%. The purpose of this study is to analyze factors associated the incidence of diabetic retinopathy in type 2 DM patients at Central Java Provincial Hospital in 2023. This research is quantitative research with a nested case control study design, using electronic medical record data from the Central Java Provincial Hospital in 2023. The variables in this study were gender, age, education level, employment status, marital status, health insurance status, BMI, DM diet, duration of DM, hypertension, other diseases, current blood glucose, and HbA1c. The analysis used was univariate, bivariate, and multivariate analysis (logistic regression). The results showed that there was association between age ≥70 years (p=0.006), DM diet (p<0.0001, OR=20.914), duration of DM (p=0.003, OR=3.010), hypertension (p=0.013, OR=2.619), other diseases including cataracts (p=0.040, OR=9.00), glaucoma (p=0.007), CHD (p=0.040, OR=9.00), and cardiomegaly (p=0.016), current blood glucose (p=0.045, OR=2.478), and HbA1c (p<0.0001, OR=6.152). DM diet is the most dominant factor associated with diabetic retinopathy in type 2 DM patients.